A study of heroic figures in selected dramatic writings of Heinrich Bőll - Gahagan, Maureen Gwendolyn (My University, 1968)
In this thesis nine dramatic works (eight radio plays and one drama) of Heinrich Bő;; are discussed in detail. An attempt has been made to show, with Menschlichkeit as a criterion, that many of the characters are heroic figures. In addition Bőll is presented as one of his own heroes.
Keywords: German Language and Literature; German Language and Literature